Implementasi Model Explicit Intruction Untuk Meningkatkan Hasil Belajar Siswa Pada Mata Pelajaran PKn di SDN 01 Kiham Batang - Rosna Wati; Aprima Tirsa; Erlin Eveline (JURNAL PENDIDIKAN DAN PEMBELAJARAN SEKOLAH DASAR, 2026)
Abstract: The research was motivated by the low learning outcomes of students in PKN subjects. The aim of the research is to determine the improvement in student learning outcomes using an explicit model of instruction in class IV of SD Negeri 01 Kiham Batang. The research method uses classroom action research with the Kemmis Mc Taggart model. This type of research uses empirical classroom action research. The research procedure includes four stages, namely: planning, action, observation and reflection. The research subjects were 6 class IV students at SD Negeri 01 Kiham Batang, consisting of 3 boys and 3 girls. The research object improves student learning outcomes using explicit instruction models. Data collection techniques is tests, observations and documentation. The research instrument used essay question sheets and lesson plan implementation sheets. The criteria for research success are reaching 85% of student scores above 70 (KKM). The research results show that using an explicit instruction model can improve student learning outcomes in class IV students at SD Negeri 01 Kiham Batang. The results of the research in cycle 1 were 3 students who completed with a percentage of 50% and 3 students who did not complete with a percentage of 50%. The results of the research in the second cycle of students who completed were 6 people with a percentage of 100%. The research results show that there is an increase in student learning outcomes in each cycle. The research conclusion is that the use of the Explicit Instruction model can improve student learning outcomes in PKn learning. Keywords: Explicit Instruction Model, Student Learning Outcomes, PKn. Abstrak: Penelitian didasari rendahnya hasil belajar siswa pada mata pelajaran PKN. Tujuan penelitian mengetahui peningkatan hasil belajar siswa menggunakan model explicit instruction di kelas IV SD Negeri 01 Kiham Batang. Metode penelitian menggunakan penelitian tindakan kelas dengan model Kemmis Mc Taggart. Jenis penelitian menggunakan penelitian tindakan kelas empiris. Prosedur penelitian meliputi empat tahapan, yaitu: perencanaan, tindakan, observasi dan refleksi. Subjek penelitian siswa kelas IV yang berjumlah 6 orang. Objek penelitian meningkatkan hasil belajar siswa menggunakan model explicit instruction. Teknik pengumpulan data menggunakan tes, observasi dan dokumentasi. Instrumen penelitian menggunakan lembar soal dan lembar keterlaksanaan RPP. Hasil penelitian diketahui bahwa dengan menggunakan model explicit instruction dapat meningkatkan hasil belajar siswa pada siswa kelas IV SD Negeri 01 Kiham Batang. Hasil penelitian pada siklus 1 siswa yang tuntas sebanyak 3 orang dengan persentase sebesar 50% dan siswa yang tidak tuntas sebanyak 3 orang dengan persentase sebesar 50%. Hasil penelitian pada siklus II siswa yang tuntas sebanyak 6 orang dengan persentase sebesar 100%. Hasil penelitian ini menunjukkan terjadinya peningkatan hasil belajar siswa pada setiap siklusnya. Kesimpulannya adalah penggunaan model explicit instruction dapat meningkatkan hasil belajar siswa dalam pembelajaran PKn. Kata Kunci: Model Explicit Instruction, Hasil Belajar Siswa, PKn.